The emergence of colonial fiscal categorizations in Peru: Forasteros and yanaconas del rey, sixteenth to nineteenth centuries - Albiez Wieck, Sarah (2020)
The article traces the emergence and further development of two related fiscal categorizations concerning indigenous peoples in the viceroyalty of Peru: forasteros and yanaconas del rey. Broadly speaking, both categorizations denoted indigenous people living outside their original communities, generally without access to communal lands, and therefore often characterized as migrants. As we will show, access to land and migration were not always and everywhere present. We analyze these social and fiscal categorizations from conquest to the early nineteenth century, occasionally addressing several related minor classifications, such as quintero, which were regionally limited. We argue that the General Visitation by Viceroy Mancera in 1645 was a turning point since it included for the first time separate lists of yanaconas del rey and forasteros within the tributary censuses.